Multiyear drought exacerbates long‐term effects of climate on an invasive ant species. Issue 10 (2nd September 2021) - Couper, Lisa I.; Sanders, Nathan J.; Heller, Nicole E.; Gordon, Deborah M.
Abstract: Invasive species threaten biodiversity, ecosystem function, and human health, but the long‐term drivers of invasion dynamics remain poorly understood. We use data from a 28‐yr ongoing survey of a Northern California ant community invaded by the Argentine ant ( Linepithema humile ) to investigate the influence of abiotic and biotic factors on invasion dynamics. We found that the distribution of L .  humile retracted following an extreme drought that occurred in the region from 2012 to 2015. The distribution of several native ant species also contracted, but overall native ant diversity was higher after the drought and for some native ant species, distributions expanded over the 28‐yr survey period. Using structural equation models, we found the strongest impact on the distribution of L .  humile was from direct effects of climate, namely, cumulative precipitation and summer maximum temperatures, with only a negligible role for biotic resistance and indirect effects of climate mediated by native ants. The increasing drought and high temperature extremes projected for northern California because of anthropogenic‐driven climate change may limit the spread, and possibly the impact, of L .  humile in invaded regions. The outcome will depend on the response of native ant communities to these climatic stressors.